The challenge of developing ecohydrological metrics for vegetation communities in calcareous fen wetland systems - Bijkerk, Ella; Regan, Shane; Johnston, Paul M.; Coxon, Catherine; Gill, Laurence W. (Frontiers in Earth Science, 2022)
Calcareous fens are peat-wetlands fed mainly by groundwater, located in topographic hollows and served by springs or seepages of water derived by contact with base-rich mineral ground. In the European Union they are protected habitats requiring special conservation measures. To better understand the environmental supporting conditions of alkaline fen habitat found in Ireland, a 2-years hydrological and hydrochemical monitoring programme was carried out on four contrasting fen sites that covered an ecohydrological gradient representing intact to highly degraded conditions. This paper presents a methodology (and its limitations) of how the evaluation of the temporal and spatial variability of the quality and hydrological dynamics associated with different representative vegetation communities within the four fens can be used to develop ecohydrological metrics for fen habitat. The conditions supporting fen habitat in “good” ecological condition, indicative of a functioning alkaline habitat, were determined and contrasted with conditions found in habitats deemed to be in “poor” ecological condition. Results indicate that an annual water level always above the ground surface within a threshold depth envelope of between 0.030 and 0.28 m is required for at least 60% of the year for healthy fen vegetation. In terms of hydrochemistry, higher concentrations of nutrients were found in the sediments at depth and the groundwater feed compared to the phreatic water table. This suggests the fens may be incorporating the incoming nutrients into their internal biogeochemical cycles and that there is a net accumulation of nutrients within the wetlands. Although envelopes of nutrient concentrations in the surface water of the fen associated with habitat in good ecological condition can be defined (e.g., dissolved reactive phosphorus concentrations of between 6 and 37 µg-P/l for PF1 habitat), these levels should be regarded as the water quality after the fen vegetation has effectively interacted with the higher incoming nutrient levels in the groundwater. Moreover, the local hydrogeological conditions that define groundwater pathways (and associated water quality impacts) in such calcareous fens, allied to the localized nature of these measurements in these field studies, makes it difficult to define groundwater water quality threshold values with any confidence.